Picturing Pollock: Photography’s Challenge to the Historiography of Abstract Expressionism - Peter R. Kalb (Journal of Art Historiography, 2012)
In the summer and fall of 1950, photographers Rudy Burckhardt and Hans Namuth documented Jackson Pollock in his studio as he was creating what have become his iconic Abstract Expressionist paintings. The photographs quickly dominated the critical discourse of the new painting and initiated a crisis in the historiography of Abstract Expressionism. This paper argues that despite being produced to serve an illustrative role for the Art News series ‘An Artists Paints a Picture’, Burckhardt and Namuth’s photographs of Pollock provide a glimpse of the analytic complexity photography offered art criticism.